Participation of Local Communities in Road Safety Through Participation Research Approach (PAR): A Case Study of Thakhlong Municipality, Pathumthani - Iamtrakul, Pawinee; Simcharean, Piriya; Jantaworn, Pornchai (Journal of Architectural/Planning Research and Studies (JARS), 2018)
Death, injury and property damage from road accidents in Thailand are still serious and multidimensional problem. For this reason, this research targeted the causes of road accidents that require public participation in local communities, with the aim of establishing a learning process together through Participatory Action Research (PAR). The case study in Thakhlong Municipality, Pathumthani Province was selected to adopt a participation process for enhancing road safety through awareness and understanding. Then, the risk areas or ‘black spots’ for road accidents were identified, based on a mapping approach, leading to a multilateral learning process towards the problems of road accidents. Eventually, an integrated approach was discovered through the cooperation of various local departments and communities to search for a sustainable solution to improve road safety. The Participatory Action Research was not only built through mutual agreement for road safety improvement, but also strengthened road safety in the local community. An approach to promote a strategy of sustainable road safety through academic institutions in collaboration with local communities could be an alternative solution to raise road safety and improve management at the local level.